2004
DOI: 10.1016/j.neuroscience.2004.01.044
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y inhibits capsaicin-sensitive nociceptors via a Y1-receptor-mediated mechanism

Abstract: Neuropeptide Y (NPY) is expressed in certain primary afferent fibers, is up-regulated in response to tissue injury and is capable of inhibiting nociceptive behavior at the spinal level. However, the spinal mechanism(s) for NPY-evoked antinociception is unknown. In this study, we evaluated the hypothesis that agonists at the NPY Y1 receptor subtype (Y1-R) inhibit exocytosis from the capsaicin-sensitive class of nociceptors. Using in vitro superfusion of rat dorsal spinal cord slices, pre-treatment with the Y1-R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 43 publications
2
21
0
Order By: Relevance
“…These results are consistent with the antibody microprobe studies of Duggan et al, who reported that microinjection of NPY into the substantia gelatinosa reduced SP-LI that was released by electrical stimulation of unmyelinated primary afferent nerves (Duggan et al, 1991). Our results also support the findings of Gibbs and Hargreaves, who reported that Y1 activation attenuated capsaicin-evoked mechanical allodynia and release of calcitonin gene-related peptide in dorsal horn slices, and attenuated bradykinin/prostaglandin E2-evoked increases in intracellular calcium levels in trigeminal ganglion neurons (Gibbs et al, 2004, Gibbs et al, 2006, Gibbs et al, 2007). Second, we measured SP release in terms of NK1R internalization, and induced the release by applying a noxious stimulus to one hind paw of the rat.…”
Section: 0 Discussionsupporting
confidence: 92%
“…These results are consistent with the antibody microprobe studies of Duggan et al, who reported that microinjection of NPY into the substantia gelatinosa reduced SP-LI that was released by electrical stimulation of unmyelinated primary afferent nerves (Duggan et al, 1991). Our results also support the findings of Gibbs and Hargreaves, who reported that Y1 activation attenuated capsaicin-evoked mechanical allodynia and release of calcitonin gene-related peptide in dorsal horn slices, and attenuated bradykinin/prostaglandin E2-evoked increases in intracellular calcium levels in trigeminal ganglion neurons (Gibbs et al, 2004, Gibbs et al, 2006, Gibbs et al, 2007). Second, we measured SP release in terms of NK1R internalization, and induced the release by applying a noxious stimulus to one hind paw of the rat.…”
Section: 0 Discussionsupporting
confidence: 92%
“…Another explanation would be that NPY is inhibiting the release of CGRP. Gibbs et al reported that pre-treating rat dorsal spinal cord slices with a NPY agonist inhibited capsaicin-induced release of CGRP [24]. These investigators demonstrated that the Y1 NPY receptor co-localized with VR1 in rat dorsal root ganglion neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Because NPY inhibits the central release of CGRP from dorsal horn slices [35], these NPY receptors are poised to regulate pronociceptive neurotransmitter release from primary afferent neurons. Furthermore, peripheral nerve injury dramatically increases spinal NPY at the central terminals of low threshold DRG neurons and their central terminals, which appears to be associated with enhanced release in the dorsal horn [36].…”
Section: Spinal Neurotransmitter Inhibition Of Neuropathic Painmentioning
confidence: 99%